Nutritional Value of Grain-Based Foods - Carcea, Marina (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Grains are fundamental in the daily diet of many people worldwide. They are used for the production of popular foods, such as bread, bakery products, breakfast cereals, pasta, couscous, bulgur, snacks, etc. Botanically, they are the seeds of plants-mainly cereals, pseudocereals and legumes. They contribute macronutrients to the human diet, mainly carbohydrates, but also proteins and lipids, and micronutrients, such as vitamins and minerals. They are also an important source of dietary fibre and bioactives, particularly wholegrains, which are important for the manufacture of high-value foods with enhanced health benefits. They can be used for the production of gluten-containing but also gluten-free products. A key objective of the food industry in producing grain-based foods is to manufacture safe, attractive products with enhanced nutritional value, to respond to consumer expectations. This book, Nutritional Value of Grain-Based Foods, contributes to existing knowledge on important ingredients such as fat substitutes and on the technological quality and nutritional role of grains and grain-based foods, such as bread, muffins and muesli bars, both gluten-containing and gluten-free.